2013
DOI: 10.1371/journal.pone.0059561
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic and Performance Effects of Caffeine Compared to Coffee during Endurance Exercise

Abstract: There is consistent evidence supporting the ergogenic effects of caffeine for endurance based exercise. However, whether caffeine ingested through coffee has the same effects is still subject to debate. The primary aim of the study was to investigate the performance enhancing effects of caffeine and coffee using a time trial performance test, while also investigating the metabolic effects of caffeine and coffee. In a single-blind, crossover, randomised counter-balanced study design, eight trained male cyclists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
142
3
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(178 citation statements)
references
References 40 publications
10
142
3
23
Order By: Relevance
“…People with heart problems are advised against taking caffeine because it increases heart rate. It can also cause heart burns because it increases gastric acid production (Hodgson et al, 2013). Taken in high amounts, caffeine can also cause insomnia, tremors, nervousness and headaches (Smith, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…People with heart problems are advised against taking caffeine because it increases heart rate. It can also cause heart burns because it increases gastric acid production (Hodgson et al, 2013). Taken in high amounts, caffeine can also cause insomnia, tremors, nervousness and headaches (Smith, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that caffeine can act as an ergo-genic aid, in long-term exercise [5][6][7][8][9]. Caffeine's primary ergo-genic mode of action is on the CNS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most research, have investigated the effect of low or moderate doses of caffeine consumption on performance, perceptual responses and Neuromuscular factors prior to endurance exercise [7][8][9]13,14]. Nevertheless, there are a few studies that considered the effect of high doses of caffeine on endurance exercise [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces effets pourraient expliquer la symptomatologie de reflux gastro oesophagien décrite par certains consommateurs de café [9]. Enfin, la caféine est dotée d'effets métaboliques sur la glycogénolyse et la lipolyse au niveau des muscles squelettiques, des reins et du foie, avec pour résultat global, une amélioration des performances physiques [10]. Outre les effets systémiques de la caféine que nous avons brièvement mentionnés, la caféine exerce un effet diurétique significatif lors d'une ingestion de 300 mg, soit 4 à 5 tasses de café [11,12].…”
unclassified